SOCIO-PEDAGOGICAL CHARACTERISTICS OF STUDYING CULTURAL HERITAGE IN NAMANGAN REGION - Ruzinov Baxtiyor Asqarovich (International Scientific and Current Research Conferences, 2024)
This article explores the socio-pedagogical characteristics of studying cultural heritage in the Namangan region of Uzbekistan. Emphasizing the significance of cultural heritage in fostering a sense of identity and continuity, this study examines the methods and approaches used to teach and preserve cultural heritage within the region. The research highlights the integration of cultural heritage into the educational curriculum, community involvement, and the role of technology in enhancing the learning experience. The findings suggest that a holistic approach involving educators, students, and the community can effectively promote the appreciation and preservation of cultural heritage in Namangan.